Análise por difração dos raios X da gedunina C28H26O, utilizando os métodos diretos - (:unkn) unknown (Universidade Estadual de Goiás, 2010)
The present work aims to develop the concepts of Crystallography as an ab-ínitio methodology needed to determine the molecular architecture from the diffraction of X-ray. The compound chosen as the target is from natural origin, the Gedunina, whose structural formula is C28H26O7, which has functions, with potential bioactive, beneficial to the development of drugs to treat diseases like, for example, cancer and malaria. The methodology used for the resolution of the compound’s crystallographic structure was the Direct Methods, with methodological tool for research on the topology of the molecular structure of Gedunina, with the potential inhibitor protein degeneration of Hps90 horsepower and the opportunity to use as pesticide. The collected informations in the diffraction experiment are organized and implemented with several algorithms that assist in the probably structure determined with a good reliability. The computing apparatus is available in the form of applications used as SHELXS and SHELXL, and others on the platform WingX. The Crystallography has a high level of refinement accumulated since the work of Max von Laue, Paul Ewald and Bragg, and other major contributors of this noble art about identifying and quantifying the intimacy of the matter’s crystalline nature. The prospects that involve Crystallography are numerous, and they have awakened the interest for the mapping process of proteins and small molecules. Regarding applications, the most obvious application is currently the process of research and drug development, in addition to genetic mapping.
Keywords: Cristalografia; Difração de raios; Metódos diretos; CIENCIAS EXATAS E DA TERRA::QUIMICA; QUIMICA::FISICO-QUIMICA